Analisis Rasio Guna Mengevaluasi Kinerja Keuangan pada PT Unilever Indonesia Tbk 2020-2021 - Laila Kamila Ramadhani; Andi Mutmainnah; Nur Afiah Fahri; Nurhadi Sidik; Hariany Idris (STIEM BONGAYA, 2022)
Abstract: This study aims to analyze the financial statements of PT UNILEVER INDONESIA Tbk. It is seen from the ratio analysis for the 2020-2021 period. Financial ratios as one of the analytical tools applied to analyze the ability of a company's financial statements. Financial ratios have advantages over other analyzes. There are different types of financial ratios; liquidity, solvency, performance, and profitability. Ratio; current, fast, money showing relatively “unhealthy” returns, debt-to-assets ratio showing “healthy” results, debt-to-equity ratio showing “unhealthy” results and inventory turnover ratio showing “healthy” results. Net yields and margins, return on assets, operating margins, return on equity, and gross margins relative to several industries are currently showing good performance; compared to the industry average.